2009
DOI: 10.1631/jzus.b0820175
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenesis effect of generation 4 polyamidoamine/vascular endothelial growth factor antisense oligodeoxynucleotide on breast cancer in vitro

Abstract: Abstract:Objective: To study the effects of the generation 4 polyamidoamine/vascular endothelial growth factor antisense oligodeoxynucleotide (G4PAMAM/VEGFASODN) compound on the expressions of vascular endothelial growth factor (VEGF) and its mRNA of breast cancer cells and on the inhibition of vascular endothelial cells. Methods: We examined the morphology of G4PAMAM/VEGFASODN compound and its pH stability, in vitro transfection efficiency and toxicity, and the expressions of VEGF and its mRNA. Methyl thiazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A full generation PAMAM dendrimer has primary amine groups on the surface (pKa =6.85) and tertiary amine groups within the core (pKa = 3.86) [31]. The high density of surface functional groups on PAMAM dendrimers presents the opportunity of functionalizing these polymers with various drugs, nucleic acids and imaging system components (Figure 2B) [3239]. PAMAM dendrimers of certain generations and surface charge can permeate the epithelial barrier of the gut, suggesting their potential as oral drug carriers [628].…”
Section: Introductionmentioning
confidence: 99%
“…A full generation PAMAM dendrimer has primary amine groups on the surface (pKa =6.85) and tertiary amine groups within the core (pKa = 3.86) [31]. The high density of surface functional groups on PAMAM dendrimers presents the opportunity of functionalizing these polymers with various drugs, nucleic acids and imaging system components (Figure 2B) [3239]. PAMAM dendrimers of certain generations and surface charge can permeate the epithelial barrier of the gut, suggesting their potential as oral drug carriers [628].…”
Section: Introductionmentioning
confidence: 99%
“…The results were very promising as the lOnm wide and homogeneously netlike dendrimer complex showed an impressive buffering ability between a pH of 5-10, a transfection efficiency of 98.76% with a charge ratio of 1:40, and no toxicity on the cells. The results showed a marked decrease in VEGF protein and mRNA (42). In another study, Liu et al confirmed the promising anticancer effects of PAMAM dendrimers when they experimented with triethanolamine (TEA) core PAMAM dendrimers to deliver heat shock protein Hsp27 siRNA successfully in (PC-3) prostate cancer cells.…”
Section: Delivery Of Biomoleculesmentioning
confidence: 90%
“…In a study of Gu et al a generation 4 polyamidoamine/vascular endothelial growth factor antisense oligodeoxynucleotide (G4PA-MAM/VEGFASODN) compound showed significantly higher transfection rate in 48 h than that of the liposome group (P \ 0.05) without obvious toxicity on the cells. More importantly, the expressions of both VEGF protein and its mRNA after G4PAMAM/VEGFASODN transfection decreased markedly [73].…”
Section: Inhibiting Gene Expression By Antisense Oligonucleotides (Asmentioning
confidence: 94%